La educación en TIC’s: Un problema de la Educación escolar y de la Educación de la vida cotidiana (2014)
This article aims to analytically approach to a complex subject of future researches. This is to build the Education ICT’s, in a modeled and relational manner, with two possible facets of education: namely, School Education and Everyday Education. Both fields are opposites but one, Everyday Education, has greater cultural relevance. Everyday Education as analytical model can provide lights in this discernment: The educational use of ICT should be culturally relevant. In this sense, we start from the recognition of the fallacies associated with the terms, and their derivatives, “Digital Culture” or “ICT Cultures”: culture is understood, not as a set of customs of a society, but the symbolic and semantic structure that articulates the men who is made with this.